Women’s local government representation in Auckland – does size matter? (Commonwealth Journal of Local Governance, 2018)
The article examines women’s local government representation following amalgamation to form a super-sized city authority, Auckland, which covers a third of New Zealand’s population. Using a gender perspective, it analyses the promise implicit in amalgamation rhetoric that democratic gaps in representation, including the gender gap, would diminish. It examines the question of whether size has made a difference. Prior to local government amalgamation, women’s representation had not significantly increased over a period of seven election cycles. Women’s descriptive and substantive representation are examined at national and city levels and the gendered implications of local government reform are considered from the perspectives of female elected representatives at councillor and local board levels. Evidence shows that local government reform has yet to be the catalyst for improving women’s descriptive and substantive representation, although there are tentative signs of entry-level improvement at community board level which raise the prospect of a pipeline effect. Interviews with elected female representatives after amalgamation show that while they do not identify themselves as speaking for women, they see themselves as women speaking for their communities and doing it better than men. The results suggest the influence of gender backlash politics and also confirm the need to think about the performance of elected women as more than ‘articulated’ representation.